Realismo Neoclássico e o Nível Doméstico: A dança das variáveis intervenientes: Neoclassical realism and the domestic level: the intervenient variable parade - Dall'Agnol, Gustavo Fornari (Faculdade de Filosofia e Ciências, 2020)
The present paper aims at theoretically exploring the domestic level in the Neoclassical Realist research program. In order to do so, it analyzes the program since its origins in the 1990 towards its most recent development, expressed by the work of Ripsman, Lobell and Taliaferro (2016). A critical review of the employment of domestic variables is realized, arguing that they are introduced in a non-systematic manner and are an obstacle for the future of the research program. Beyond that, it will be proposed, that Neoclassical Realism, as a possible solution, reorganizes its domestic level variables employed in their analysis and theoretical constructions, in a manner of giving primacy to variables closer to the realist ontology and epistemology. The conclusion is that this is one way of overcoming the critics towards the research program, which from the perspective of this work, has been contributing decisively to the study of international politics and can keep doing so.